Emlanjeni: Reconnecting people with the landscape to promote social interaction - Damane, Sisipho kanya (School of Architecture, Planning and Geomatics, 2024)
This thesis seeks to explore the idea of reconnecting the people of Ngqwarhu, Cofimvaba, Eastern Cape, with the landscape. This thesis will explore how a river from this village played a very important role to its people. The river was the centre of the village. This will further explore how rivers have historically served as a means of connecting people and explore ways people can interact with the natural environment. In this local context, the river functioned as a vital water resource and a space that connects communities. This connection provides a sense of identity and belonging in the village. The past is a rich source of knowledge, a record of human experience that we can learn from and draw inspiration from. This thesis resurfaces the landscape memories by introducing social interaction that will reconnect the community. The disconnection of human-nature relationships in this village is the lack of development, conservation of culture, migration, and a lack of recreational opportunities. The river used to function as a vital water resource, it was used as a main space to wash clothes and to get drinking water. The river was not only used for essential needs, but it was an active space for connecting, socializing, and gathering. In the process of getting water and doing laundry, people used that time to socialize with one another. There were tangible and intangible reasons that brought people to the river. Without the crucial need to go to the river, the connection between the people and the landscape is fading away. This thesis hopes to reconnect the people of the village not only through social interactions in the natural environment but to one another. This will also explore the significance of restoring the relationship between individuals and the landscape that surrounds the village. This thesis investigates the multifaceted benefits of such reconnection, as it can create opportunities, healthier, happier, and more sustainable communities. Keywords: The Landscape, Sense of Place, Memory, Storytelling